ANALISIS PENGARUH SELF ESTEEM DAN SELF EFFICACY TERHADAP SEMANGAT KERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Safitri, Dhanis Bidalia; Violinda, Qristin; Putri, Noventia Karina (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2025)
The purpose of this study is to analyze the influence of Self-esteem, Self-efficacy, on employee work spirit, to analyze the influence of Self-esteem, Self-efficacy and work spirit on employee job satisfaction, to analyze the influence of Self-esteem on employee work spirit through job satisfaction and to analyze the influence of Self-efficacy on employee work spirit through job satisfaction. This study uses a quantitative descriptive research method. The sample of this study amounted to 87 respondents. The results of this study can be concluded that Self-esteem has a negative effect on employee work spirit, Self-efficacy has a positive effect on employee work spirit, Self-esteem, Self-efficacy and work spirit have a positive effect on employee work satisfaction, Self-esteem has a positive effect on employee work spirit through job satisfaction and Self-efficacy has a positive effect on employee work spirit through job satisfaction”.